Effect of N and P fertigation on fruit yield and quality of kinnow - KUMAR, ANIL; SINGH, HARMINDER; PATHANIA, SHASHI (The Indian Journal of Agricultural Sciences, 2023)
The effects of N and P fertigation on productivity and quality of kinnow mandarin were investigated in southwestern part of Punjab at the Regional Research Station, Abohar of Punjab Agricultural University, Ludhiana, Punjab during 2018–2020. Different combinations of the recommended dose (RD) of N and P, viz. 100, 75, and 50% were applied in equal splits at 5 stages of kinnow trees (February–October) and compared with conventional flood irrigation plus soil fertilization. The results showed that fertigation resulted in higher nutrient uptake, total leaf chlorophyll content, and vital physiological processes as compared to conventional practices. Tree volume under fertigation was about 29% higher than conventional practices. The data also revealed a significantly higher fruit set (20.13%), fruit weight (168.6 g), and fruit size (7.68 cm) as compared to flood irrigation plus soil fertilization. Fruit yield was about 33% higher in fertigated trees over flood irrigation and soil fertilization. Further, fruit quality parameters especially in terms of per cent juice, TSS-acid ratio, and ascorbic acid concentration were also superior in fertigated trees. In addition, fertigation resulted in a higher proportion of economic fruit grades over conventional flood irrigation and soil fertilization. The results suggest that fertigation @75% of N and P of recommended dose exhibited higher growth and productivity of kinnow mandarin, saving 25% N and P usage with better grade and higher quality of kinnow.